Effective parameters on strength of fibre reinforced soil - Chegenizadeh, Amin; Nikraz, Hamid (Trans Tech Publications, 2012)
Soils and their related behavior has always been the subject of many studies. Recent researches show some interests in investigation of inclusion of randomly distributed fiber in soil. Reinforcing subgarde in pavement systems has always been an issue. This study focuses on effect of fiber inclusion on the strength of subgrade material. Natural fiber and plastic fibre were used for this investigation. Fiber contents and length have been changed during these tests. The fiber percentage varied from 0 % (for unreinforced samples) to 2% and fiber length varied from 10mm to 30mm. UCS tests and compaction tests were carried out to investigate behavior of the composite under different condition. The fiber length and fiber content found to play important rule on the strength of fiber reinforced composite. Furthermore it was observed that ductility of sample increased by fiber inclusion.